Study on the Structure and Tribological Behavior of Zn - Ni Coating by Pack - Cementation - ZHANG Jin, LIN Yuan - hua, GUO Meng - xin, XIANG - Huan, RAN Xue - lin, HUANG Min (Cailiao Baohu)
In order to improve the friction and wear properties of 45 steel’s surface surface, a Zn - Ni coating was prepared on 45 steel’s surface by pack - cementation method. The thickness, micro - morphology, phase composition and element distribution of Zn - Ni coating were studied by X - ray diffraction(XRD), scanning electron microscope(SEM) and energy dispersive spectrometer. The hardness of the coating was analyzed by micro Vickers hardness tester. The friction and wear behavior of the coating was tested by multifunctional material surface performance instrument under the different normal pressure with three different grinding balls: GCr15, Al2O3 and Si3N4. Results showed that the thickness of Zn - Ni coating was about 98 μm, and the phase compositions of the coating were mainly FeZn10.98, FeZn8.87, respectively. The cross - section hardness of Zn - Ni coating reached ranging from 358～615 HV0.98 N. In the reciprocating friction experiment, the wear forms of Zn - Ni coating were mainly adhesion and abrasive wear when reciprocating friction with GCr15 grinding ball; the wear forms were mainly abrasive wear when reciprocating friction with Al2O3 grinding ball. Furthermore, the form of Zn - Ni coating was mainly the tribo - chemical process when reciprocating friction with Si3N4 grinding ball.